Effects of institutional quality and political risk on the renewable energy consumption in the OECD countries. (December 2022) - Wang, Erhong; Gozgor, Giray; Mahalik, Mantu Kumar; Patel, Gupteswar; Hu, Guoheng
Abstract: Higher institutional quality and lower political risk are the essential drivers of rescuing the resource curse and achieving sustainable development since these variables can also affect energy demand via energy transitions. Given this background, this paper examines the effects of novel measures of institutional quality and political risk on renewable energy consumption in the panel dataset of 32 Organisation for Economic Co-operation and Development (OECD) member countries from 1997 to 2019. It is observed that a higher level of institutional quality and per capita income increase renewable energy consumption. In addition, economic globalisation and political risk are negatively associated with renewable energy consumption in the long run. Therefore, the policymakers in the OECD countries should consider the role of institutional effectiveness and political risks in renewable energy demand function to ensure a cleaner natural environment in the long run. Highlights: We examine the determinants of renewable energy consumption We focus on the role of institutional quality and political risk We use the panel data of 32 OECD countries from 1997 to 2019 Institutional quality and per capita GDP promote renewable energy consumption